Gendered and Sexual Violence in and beyond South Asia. Issue 1 (June 2016) - Chatterji, Angana P.
Spectacular and quotidian gendered and sexualized violence in states and collectives of the (post)colony holds in place fraught, unjust histories and relations between elites and subalterns, majoritarian subjects and non-dominant 'Others'. At the intersections of nationalist and decolonial confrontations, such violence regularizes states of emergency and exception. The following excerpts are curated from the co-edited and co-contributed monograph, Conflicted Democracies and Gendered Violence: The Right to Heal. The monograph elucidates the centrality of political and foundational violence in the governance of conflicted democracies in the (post)colony and calls attention to the urgent need for transformation. Through oral history, archival and legal research undertaken over three years, this interdisciplinary work espouses the right to heal. It underscores the need for immediate, transitional and transformative justice mechanisms in conflicted democracies to address protracted conflict (focusing on their internal dimensions) and social upheaval (in Kashmir, Punjab, Gujarat and Odisha). India serves as an exemplar. The issues pertinent to contemporary India are both specific to it and generalizable across cultural and discursive spaces beyond it. They are shared across nation states with varying forms of government and diverse relations to social difference. The excerpts below outline certain conceptual 'keywords' from the first chapter that provide a framework for engaging the comparative and situated issues of gendered and sexualized violence and oral histories of victimized-survivor subjects in the monograph.